2022
DOI: 10.1177/08862605211067018
|View full text |Cite
|
Sign up to set email alerts
|

Student-Athletes’, Coaches’, and Administrators’ Perspectives of Sexual Violence Prevention on Three Campuses with National Collegiate Athletic Association Division I and II Athletic Programs

Abstract: Research has found associations between intercollegiate athletics and risk for sexual violence, and that sexual violence is more pervasive at colleges and universities with National Collegiate Athletic Association (NCAA) Division I athletic programs, relative to NCAA Division II, NCAA Division III and no athletic programs. Simultaneously, sports involvement is linked with prosocial values and there are documented developmental benefits of sports participation. College athletic programs hold promise for fosteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“… 8. Previous work has been published or presented by our UC Speaks Up research team, focusing on how athletes perceive SVSH prevention efforts (Carey et al, 2022) and the importance of including alcohol and drug education in SVSH prevention (Swendeman et al, 2020). …”
mentioning
confidence: 99%
“… 8. Previous work has been published or presented by our UC Speaks Up research team, focusing on how athletes perceive SVSH prevention efforts (Carey et al, 2022) and the importance of including alcohol and drug education in SVSH prevention (Swendeman et al, 2020). …”
mentioning
confidence: 99%
“…The present study builds on this previous work, providing one of the first comprehensive assessments of self-reported experiences with IV in sport by currently competing college athletes while in the middle of their college career. It expands on emerging research among US college athletes that has, until now, primarily focused on the potentially devastating consequences of sexual abuse as a form of IV . Recent research from the Commonwealth Games Federation suggests that athletes who are actively engaged in highly competitive training are in a unique period of their lives .…”
Section: Discussionmentioning
confidence: 99%
“…Among elite athletes competing at the top of their sport, research suggests that as many as 75% will experience IV at some point during their career, particularly those who identify as being female, having a disability, belonging to historically underrepresented racial and ethnic groups, and having a nonheterosexual sexual orientation . Among youth or adolescent and collegiate athletes, the prevalence of IV has been reported to be upward of 33%, with a substantial proportion of the literature focusing on experiences of sexual abuse as a form of IV …”
Section: Introductionmentioning
confidence: 99%
“…Studies by Carey et al (2022) and Fenn et al (2022) offer important qualitative evidence regarding perceptions of SV prevention and intervention programs from coaches and administrators in college and youth athletics, respectively. Data from colleges and universities indicate that coaches and administrators have good awareness of programs and policies, but little knowledge related to student perceptions of these campus efforts.…”
mentioning
confidence: 99%
“…Data from colleges and universities indicate that coaches and administrators have good awareness of programs and policies, but little knowledge related to student perceptions of these campus efforts. Additionally, campus SV prevention activities were largely independent of the campus sport entities (Carey et al, 2022). College-athletes in this same study indicated low levels of comfort in disclosing or seeking support from coaches or campus SV intervention services among those violated, and many felt that sport-based policies and trainings to address SV are largely ineffective.…”
mentioning
confidence: 99%